Hubungan Optimisme dan Grit Calon Taruna Akademi Angkatan Udara (AAU) di LANUD ‘X’ Kota Bandung - Evi Ema Victoria Polii; Muhamad Irhas Dirgantara (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2020)
This research aims to determine the relationship between optimism and grit on the Air Force Academy (AAU) cadet candidates (catar) in Lanud 'X' city of Bandung. There were 104 respondents who participated in this study with ages ranging from 18-21 years. This study uses a correlation research design. The optimism questionaire is compiled by researchers themselves based on the theory of optimism by Seligman (2006). Researchers used grit questionaire designed by Prameswari and Vivekananda (2017) based on Duckworth's grit theory (2007). The data analysis technique used in this study was theta wilcoxon correlation test. The results showed that there was a significant relationship between optimism and grit with a correlation coefficient of 0.324, which means it has moderate relationship strength. This means that an optimistic catar views in the face of both good and bad events will be accompanied by a high degree of grit and vice versa.